REDUCING THE RISK OF WELL INTEGRITY INCIDENT BY INTEGRATING TOPSIS AND AHP MULTICRITERIA DECISION-MAKING ANALYSIS - Ragil Sudira Wardana; Manahan Siallagan; Raka Sudira Wardana (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2021)
With current oil price downturn many oil wells become uneconomic. These uneconomic wells are left in an inactive state and become idle wells. Idle well is an environmental liability due to its risk of well integrity problems. Impacted by the downturn, the number of idle wells in the industry has been increasing in the industry. One of the solutions to mitigate these liabilities is by conducting plug & abandonment (P&A) on high-risk idle wellss. This research develops a combined framework of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) with the Analytic Hierarchy Process (AHP) as a risk assessment framework to prioritize high-risk idle wells for the P&A activity. In the assessment framework, surface condition, subsurface condition, and public exposure factors are taken as evaluation criteria to determine the risk level. The result of this research is 247 idle wells considered as high-risk wells and submitted as P&A candidates. The empirical result from this research can serve as a reference for oil companies in conducting a risk assessment on idle wells to design the proper activities to reduce environmental liabilities.